When Values Shape Visits: Modeling Psychosocial and Religious Drivers of Sustainable Tourism - Mayvita, Prihatini Ade; Syahrani, Syahrani; Abriano, Nova; Noor, Dewi Ariefah (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study develops and empirically tests an integrative model examining the influence of psychosocial factors and religious values on sustainability perceptions and tourist visit attractiveness in Indonesian tourism destinations. Grounded in the Theory of Planned Behavior (TPB) and Value-Belief-Norm Theory (VBN), the model integrates tourist attitudes, social norms, and religious values as key antecedents shaping perceptions of sustainability, which subsequently influence visit intentions. Data were collected through a survey of 1,014 domestic tourists who had previously visited sustainable tourism destinations across Indonesia. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess structural relationships among latent variables and to examine the mediating role of sustainability perceptions. The results indicate that all hypothesized relationships are statistically significant, with sustainability perceptions demonstrating a strong mediating effect between attitudes, social norms, religious values, and visit attractiveness. These findings highlight the critical role of spiritual and social dimensions in shaping tourists’ evaluations and preferences toward sustainable tourism destinations. The study contributes theoretically by extending the applicability of TPB and VBN frameworks within the sustainable tourism context. Practically, the findings offer strategic insights for destination managers and policymakers to incorporate value-based and religiously informed approaches in developing and promoting sustainable tourism destinations in Indonesia.